Price fairness: square equity and mean pricing - Dubravko Radic (Journal of Revenue and Pricing Management, 2023)
Prices have a leverage effect on firm profits. Prices, however, have also an impact on customer's perceived price fairness and thus indirectly on firm's bottom line. A growing body of literature shows this. Papers on the level of the fair price, however, are rather scarce. Based on different concepts of justice, two levels of fair prices are proposed: square equity and mean prices. I run an experiment which shows that both are considered fairer than cost-based or value-based prices. The results can be used to assess fairness implications of prices ex ante and hence complement traditional pricing approaches.
Keywords: 330; Price fairness; Proportional justice; Equity theory; Distributive justice; Value-based pricing; Cost-based pricing